Study of air pollution of Isfahan based on NO2 measured data by OMI Satellite sensor - Atefeh Shahmohammadi; Ali Bayat; Saeed mashhadizadeh Maleki (تحقیقات کاربردی علوم جغرافیایی)
Air pollution is one of the major problems in large cities, which can be harmful to human health and the environment. Isfahan is one of the most polluted cities in Iran. Its geographic location and low wind speed, industrial activities, transportation, agriculture, and other human activities have created critical air pollution conditions for the city. Nitrogen dioxide is an important pollutant of air pollution, which is monitored using ground stations and satellite measurements. In this paper, daily data of nitrogen dioxide from Ozone Monitoring Instrument (OMI) satellite sensor, wind and surface temperature of Isfahan Meteorological Station data were used between October 2004 and May 2016. The average amount of nitrogen dioxide in the measured range is .The highest amount of nitrogen dioxide ( ) was observed in December and the lowest ( ) was observed in July. The standard deviation of the winter season ( ) is higher than the summer season ( ). The correlation coefficient of nitrogen dioxide with wind and temperature was -0.41 and -0.54, respectively, which indicates the higher importance of temperature in nitrogen dioxide changes. After the formation of the time series, the average monthly nitrogen dioxide content was determined using spectral analysis of least squares of statistically meaningful peaks corresponding periods. These statistically meaningful peaks corresponding periods have been eliminated from the mean monthly nitrogen dioxide time series, and with the linear fit on the residual time series, the trend has been calculated. The nitrogen dioxide trend for Isfahan is per year with 95% confidence.